Pharyngeal airspace in patients undergoing orthognathic surgery for mandibular advancement - Guilherme dos Santos Trento; Fernando Anunziato Ogg de Salles Santos; Leandro Eduardo Klüppel; Delson João da Costa; Nelson Luis Barbosa Rebellato; Rafaela Scariot (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the increase of pharyngeal airway space (PAS) in patients undergoing mandibular advancement. Methods: A retrospective cross-sectional study was performed in thirteen patients who underwent mandibular advancement and were evaluated by cephalometric tracing in pre and postoperative lateral radiographs. In cephalometric tracing, the PAS was assessed by measuring the distance from the lower portion of the soft palate to the posterior pharyngeal wall (UP-PHW) and from the tongue base to the posterior pharyngeal wall (TB-PHW). Results: Patients' age ranged from 22 to 42 years with an average of 28.54 ± 2.23 years. A preoperative mean of 9.20 ± 4.56 mm in the UP-PHW measure and 10.53 ± 5.84 mm in the TB-PHW measure were obtained. The mean values found for those measurements in the postoperative period were 11.61 mm and 13.95 mm, respectively. There was an average increase of 2.4 mm in the UP-PHW and of 2.95 mm in the TB-PHW. The mean mandibular advancement in evaluated patients was 5 mm. There was no statistical correlation between PAS increase and the amount of mandibular advancement for UP-PHW (p=0.058) and TB-PHW (p=0.53), as there was no such correlation either between PAS increase and the age of patients for UP-PHW (p=0.16) and TB-PHW (p=0.26). A greater effect of the retrolingual dimension in mandibular advancement was observed, with an average increase of 24.52% while in the retropalatal dimension an average increase of 20.75% was obtained. Conclusions: Surgical advancement of the mandible increases the size of the pharyngeal airway space.